2022
DOI: 10.1021/acsomega.2c01820
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome Profiling Identifies Prognostic Hub Genes as Therapeutic Targets of Glioblastoma: Evidenced by Bioinformatics Analysis

Abstract: Glioblastoma (GBM) is the most devastating and frequent type of primary brain tumor with high morbidity and mortality. Despite the use of surgical resection followed by radio- and chemotherapy as standard therapy, the progression of GBM remains dismal with a median overall survival of <15 months. GBM embodies a populace of cancer stem cells (GSCs) that is associated with tumor initiation, invasion, therapeutic resistance, and post-treatment reoccurrence. However, understanding the potential mechanisms of stemn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 132 publications
1
5
0
Order By: Relevance
“…Differentially expressed genes were signi cantly enriched in signaling pathways that promoted tumorigenesis in GBMLGG, including the tyrosine kinase, Ras, PI3K-Akt, and MAPK signaling pathways (23,24). The enrichment of the genes in synaptic and axon guidance pathways suggested that the tumorigenic effects of EFNA4 were related to the promotion of cell proliferation and remodeling of neural networks in GBMLGG (25). In addition, we found an enrichment of the differential genes in the neuroactive ligand-receptor interaction pathway, in which the increased activity was related to enhanced invasiveness in GBM(26).…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed genes were signi cantly enriched in signaling pathways that promoted tumorigenesis in GBMLGG, including the tyrosine kinase, Ras, PI3K-Akt, and MAPK signaling pathways (23,24). The enrichment of the genes in synaptic and axon guidance pathways suggested that the tumorigenic effects of EFNA4 were related to the promotion of cell proliferation and remodeling of neural networks in GBMLGG (25). In addition, we found an enrichment of the differential genes in the neuroactive ligand-receptor interaction pathway, in which the increased activity was related to enhanced invasiveness in GBM(26).…”
Section: Discussionmentioning
confidence: 99%
“…The pathway enrichment analysis approach intends to annotate signaling pathways of the previously identified differential genes using the KEGG database and to retrieve all signal transduction pathways in which the genes participate. The significance level ( p value) and misjudgment rate (FDR) of each signal route then were calculated using Fisher’s exact test and multiple comparison tests [ 21 ]. The enriched gene count ≥ 2 and the level p < 0.05 were judged meaningful for GO terms and KEGG pathways in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The higher expression of screened hub genes namely TP53 (HR = 1.9; log-rank P = 3.1e-07), CDK1(HR = 4.8; log-rank P = 0), UBA52(HR = 3; log-rank P = 2.2e-16) and UBB (HR = 2.8; logrank P = 1.8e-15) mRNAs indicates the worst survival in the LGG and GBM patients (Fig. 3) [12]. This nding suggests that increased expression levels of these four genes at the time of diagnosis may signal a poor prognosis, potentially leading to a reduced overall survival rate among glioma patients except SRC (HR = 0.53; log-rank P = 0.00024).…”
Section: Survival Analysismentioning
confidence: 98%
“…The PPI network analysis aids in correlating the relationship between biological modules and the signi cance of proteins [12,17]. The STRING module in Cytoscape v3.9.1 software was utilized to construct the PPI network.…”
Section: Ppi Network Construction and Hub Gene Identi Cationmentioning
confidence: 99%
See 1 more Smart Citation